Seismic behaviour of non-rectangular structural RC wall in the weak axis - Zhang, Zhongwen (2018)
Structural reinforced concrete (RC) walls can have very different lengths and widths. Previous investigations have focused on the seismic properties of structural RC walls in the strong axis in which the length of the wall is greater than the width of the wall. The seismic behaviour of structural RC walls in the weak axis, where the wall length is less than its width, is insufficiently investigated. This paper reports on experimental studies on the seismic behaviour of two non-rectangular RC walls loaded in the weak axis. The experimental results are presented in terms of cracking patterns, failure mechanisms, hysteresis responses, the component of deformation and the distributions of vertical strains in the flange. The experimental results are discussed, and emphasise the accuracy of existing design methods for non-rectangular RC walls in the weak axis, including design methods for the stiffness, the shear lag effect and the shear strength.